1995
DOI: 10.1161/01.cir.92.4.1005
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous and Exogenous Nitric Oxide Protect Against Intracoronary Thrombosis and Reocclusion After Thrombolysis

Abstract: Increasing NO production or giving an NO donor may inhibit platelet aggregation and delay intracoronary thrombus formation and reocclusion after thrombolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 46 publications
1
30
0
2
Order By: Relevance
“…Exogenous delivery of nitric oxide, by administration of a nitric oxide donor, has been shown to reduce thrombus formation. 34,35,54 The suppression of PAI-1 released by platelets 36,37 and by VSMCs (current report) may contribute to this nitric oxide effect by promoting fibrinolysis. Consistent with this hypothesis, nitric oxide synthase inhibition has been reported to increase plasma PAI activity in environmentally stressed rats.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Exogenous delivery of nitric oxide, by administration of a nitric oxide donor, has been shown to reduce thrombus formation. 34,35,54 The suppression of PAI-1 released by platelets 36,37 and by VSMCs (current report) may contribute to this nitric oxide effect by promoting fibrinolysis. Consistent with this hypothesis, nitric oxide synthase inhibition has been reported to increase plasma PAI activity in environmentally stressed rats.…”
Section: Discussionmentioning
confidence: 63%
“…In addition to regulating vascular tone, atrial natriuretic factor (ANF), C-type natriuretic peptide (CNP), and nitric oxide-generating compounds inhibit VSMC growth and migration in vitro [27][28][29][30] and reduce neointimal formation after balloon catheter-induced vascular injury. 31,32 Nitric oxide has also been shown to provide antithrombotic activity [33][34][35] and reduce PAI-1 released from platelets. 36,37 As such, exogenous local delivery of nitric oxide synthase and CNP has been proposed as a treatment to reduce restenosis.…”
mentioning
confidence: 99%
“…Previous findings showed that NO release was increased in coronary artery myocardial ischemia (19)(20)(21). By contrast, other authors found that NO release was decreased (22,23). The function of endothelium plays an important role in maintaining stability and normal blood flow dynamics.…”
Section: Discussionmentioning
confidence: 87%
“…NO is reported to have many cardioprotective effects on ischemia and reperfusion injury (21)(22)(23)(24)(25)(26). Thus, enhancement of NO production during ischemia and reperfusion by ACE inhibitors may reduce ischemia and reperfusion injury (27,28).…”
Section: Effects Of Ace Inhibitors On Myocardial Infarct Sizementioning
confidence: 99%